Relationship between perceived procedural justice, communications about pay systems and job performance - Ismail, Azman; Mat Junoh, Adanan (2005)
Compensation management literature highlights that communication is used by employers to deliver information about pay systems to employees. Although communication about pay systems is important, its effect on individual’s performance is vague when feelings of procedural justice are present in organizations. Based on this literature, a conceptual framework for this study is developed and tested using data gathered from qualitative (in-depth interview) and quantitative (survey questionnaire) research methods. This study involved a sample of 334 employees from seven Malaysian private institutions of higher learning. The outcome of moderated hierarchical regression analysis shows that the inclusion of procedural justice into analysis increases the effect of communication about pay systems on job performance.